The grammar of words : an introduction to linguistic morphology - Booij, G. E. (Oxford Textbooks in Linguistics, 2005)
What is linguistic morphology?. 1. Morphology: basic notions. 2. Morphological analysis. Word formation. 3. Derivation. 4. Compounding. Inflection. 5. Inflection. 6. Inflectional systems. Interfaces. 7. The interface between morphology and phonology. 8. Morphology and syntax: demarcation, interaction and interface. 9. Morphology and semantics. Morphology and mind. 10. Morphology and psycholinguistics. 11. Morphology and language change. References. Language index. Subject index.